مشاهدة أفلام الكرتون وآثارها على سلوكيات الأطفال - زكية, قويدر; احلام, سمينة (University of Eloued جامعة الوادي, 2019)
"تناولت الدراسة موضوع : ""مشاهدة أفلام الكرتون وأثرها على الأطفال من خلال قناة كرتون نتورك بالعربية""، دراسة ميدانية على عينة من السنة الخامسة ابتدائي . اعتمدنا في هذه الدراسة المنهج الوصفي من أجل جمع البيانات التي تم جمعها عن طريق الاستمارة التي أجريت على المبحوثين، وعلى استمارة الاستبيان كأداة لجمع المعلومات تكون من 31 سؤال، حيث وزعت عينة الدراسة على 50 تلميذ وتلميذة بطريقة قصدية، وقد توصلت الدراسة إلى أهم النتائج التالية. - أن القناة تساهم في إثراء الرصيد اللغوي لدى أفراد العينة في التكلم باللغة العربية الفصحى . - أن الطفل يشاهد القناة للتسلية والترفيه ومليء أوقات الفراغ . - أن غالبية أفراد العينة يقومون بتقليد المشاهد المعروضة، وذلك بتقليد بعض السلوكيات الجيدة والسيئة . - أن القناة لم تراعي الجوانب التربوية والتعليمية فيما تبثه لطفل . " "the Study waz deliberate to 50 students in a deliberate manner. The study reached the following important results: All members of the eye watch Cartoon Network in Arabic . Contribute to enrich the linguistic balance of the sample in learning in classical Arabic . That the child watching the channel for entertainment and entertainment and full of leisure . – The majority of leisure sample imitate the scenes presented ,by mimicking some good and bad behaviors . That the channel does not undermine the educational and educational aspects of a child. Summary Of the Study Summary Of the Study: The study dealt with the subject: Watching cartoon films and their implications on the children of Muslims through Cartoon network Arabic , a field study on a sample of the fifth year of primary .In this study , we used the descriptive approach and the questionnaire as a tool for gathering information from 31 question. The sample of the study was distributed to 50 students in a deliberate manner . The study reached the following important results : All member of the eye watch Cartoon Network in Arabic . Contribute to enrich the linguistic balance of the sample in learning in classical Arabic. "
مذكرة ماستر تخصص دعوة واعلام
Keywords: سلوك، كرتون، طفل، أثر.; Behavior- Cartons-Child-Effect.